Handbook of religion and health - Koenig, Harold G. (Oxford University Press, 2001)
This book, the first of its kind, reviews and discusses the full range of research on religion and a variety of mental and physical health outcomes. Based on this research, the authors build theorectical models illustrating the various behavioural, psychological, and physiological pathways by which religion might affect health. They also review research that has explored the impact of religous affiliation, belief, and practice one use of health services and compliance with medical treatment. Finally, they discuss the implications of these findings, examine a number of possible clinical applications, and make recommendations for future research in this area